2007
DOI: 10.1158/0008-5472.can-07-1887
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Proliferation and Chromosomal Instability Signature in Anaplastic Thyroid Carcinoma

Abstract: Here, we show that the anaplastic thyroid carcinoma (ATC) features the up-regulation of a set of genes involved in the control of cell cycle progression and chromosome segregation. This phenotype differentiates ATC from normal tissue and from well-differentiated papillary thyroid carcinoma. Transcriptional promoters of the ATC up-regulated genes are characterized by a modular organization featuring binding sites for E2F and NF-Y transcription factors and cell cycledependent element (CDE)/cell cycle gene homolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 40 publications
3
144
0
1
Order By: Relevance
“…20,21 Y/CCAAT is Enriched in Promoters of 'Cancer' Genes Analysis of transcriptome profiles during cellular transformation identified the Y/CCAAT box as over-represented in promoters of genes overexpressed in diverse types of cancers, breast, colon, thyroid, prostate and leukemias. [22][23][24][25][26][27][28][29] Treating cells with cytotoxic drugs, or overexpressing growth suppressors, led to the downregulation of genes with CCAAT in their promoters. 30,31 However, it is important to remark that these exercises were performed with matrices included in TRANSFAC and JASPAR; hence, they could be highly biased, as the lists of transcription factor-binding sites (TFBS) present in databases certainly do not recapitulate all possible TF-binding sequences.…”
Section: Y and Ccaat: Two Names One Entitymentioning
confidence: 99%
“…20,21 Y/CCAAT is Enriched in Promoters of 'Cancer' Genes Analysis of transcriptome profiles during cellular transformation identified the Y/CCAAT box as over-represented in promoters of genes overexpressed in diverse types of cancers, breast, colon, thyroid, prostate and leukemias. [22][23][24][25][26][27][28][29] Treating cells with cytotoxic drugs, or overexpressing growth suppressors, led to the downregulation of genes with CCAAT in their promoters. 30,31 However, it is important to remark that these exercises were performed with matrices included in TRANSFAC and JASPAR; hence, they could be highly biased, as the lists of transcription factor-binding sites (TFBS) present in databases certainly do not recapitulate all possible TF-binding sequences.…”
Section: Y and Ccaat: Two Names One Entitymentioning
confidence: 99%
“…Although derived from follicular epithelium of the thyroid gland, ATC cells do not retain any biological feature of the original cell type as a result of multiple mutational events leading to dedifferentiation. A number of gene expression studies in ATC yielded evidence of the upregulation of genes involved in cell cycle progression and chromosome segregation, among which were the Aurora kinases (Salvatore et al 2007, Wiseman et al 2007, Rusinek et al 2011. In particular, Aurora-A has been identified among the most frequently and strongly overexpressed proteins in ATC, and high expression of Aurora-B has been also reported (Sorrentino et al 2005, Ulisse et al 2006, Wiseman et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanistic insights into the regulation of SAC genes remain poorly understood. Using microarray analyses, at least two independent studies have identified UBE2C as a putative transcriptional repression target of p53 (11,27). Besides being an important gene in the spindle assembly checkpoint pathway, UBE2C has also been well implicated in multiple cancers (28).…”
mentioning
confidence: 99%